Detection of PSTVd and TCDVd in seeds of tomato using real‐time RT‐PCR. (April 2015) - Bakker, D.; Bruinsma, M.; Dekter, R.W.; Toonen, M.A.J.; Verhoeven, J. Th. J.; Koenraadt, H.M.S.
<x xml:space="preserve">Abstract</x> Worldwide outbreaks of pospiviroids in potato and tomato have increased the need for a reliable test for the detection of pospiviroids in seeds. This study describes the development and validation of a sensitive and fast test for the detection of Potato spindle tuber viroid (PSTVd) and Tomato chlorotic dwarf viroid (TCDVd) in tomato seeds. The test is based on RNA isolation using a commercial kit and is suitable for routine application. The test is able to detect one PSTVd or TCDVd contaminated seed in sub samples of 1000 seeds and results were both repeatable and reproducible.